(3YbO GdaQGFO ajeG ddeKdK ef GdahGFOs - (3GdOefghQj , CMeO Hf YHO GdefYe Hf jhSa Hf UjGe GdOefghQj, SQGL GdOjf,J (B1192 (3g` s ((3Ydi Hf eMeO Gdefhai s)
(3ChdgG (B:s
(3hHYO ajbhd GdeJedb Ydi HGH aVdg GdYdi deG JaVd Ph GdLdGd hGdEcQGe Ydi GdOhdg GdYdjg s
(3BNQgG (B:s
(3aGUHQ MJi jaQZ GdONGf , hYdGeI GdELGHg Cf GdSjHI JOhQ jejfkG hdcf dGHO ef JeGe GdYed s
(3Cdag ddhRjQ GdBYXe Ydi HGTG Hf fhM CafOi Mcje HGTGs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B303s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B371 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B154 s
Keywords: (3GdMQha h GdChaGbs